Determination of cefotaxime, cefoperazone, ceftazidime and cefadroxil using surface plasmon resonance band of silver nanoparticles (Brazilian Journal of Pharmaceutical Sciences, 2018)
The aim of this work is to evaluate simple, sensitive, effective and validated procedures for the determination of cefotaxime, cefoperazone, ceftazidime and cefadroxil. In this study, the methods based on the ability of the cited drugs to reduce Ag+ ions to silver nanoparticles (Ag-NPs) in the presence of Polyvinyl Pyrrolidone (PVP) as a stabilizing agent producing very intense surface plasmon resonance peak of Ag-NPs (λmax. = 410-430 nm). The plasmon absorbance of the Ag-NPs allows the quantitative spectrophotometric determination of the cited drugs. The calibration curves are linear with concentration ranges of 0.4-3.2, 1-8, 0.5-4.0 and 1.5-9.0 µg/mL for cefotaxime, cefoperazone, ceftazidime and cefadroxil, respectively. Apparent molar absorptivity, detection and quantitative limits are calculated. Applications of the proposed methods to representative pharmaceutical formulations are successfully presented. The extracellular synthesis of nanoparticles is fast, and the method doesn’ t require various elaborate treatments and tedious extraction procedures.